Enhanced magnetism and persistent insulating state in Mn doped Sr2IrO4. (8th June 2022) - Li, Yaodong; Niu, Rui; Xu, Feng; Zhen, Weili; Huang, Hui; Wang, Jingrong; Zhu, Wenka; Zhang, Changjin
Abstract: The influences of Mn substitution at the Ir site of Sr2 IrO4 are investigated via a comprehensive study of the variation of structural parameters, the transport and magnetic properties of the Sr2 Ir1− x Mn x O4 samples. The incorporation of Mn leads to an increase of the in-plane Ir–O–Ir bond angle, while it is not sufficient to drive the Mott-insulating state to a metallic state. Interestingly, we find a coexistence of Ir 4+ –O 2− –Ir 4+ super-exchange interaction and Mn 3+ –O 2− –Mn 4+ double exchange interaction in x ⩾ 0.06 samples. The Mn 3+ –O 2− –Mn 4+ ferromagnetic domains are isolated by the Ir 4+ –O 2− –Ir 4+ antiferromagnetic areas, leading to a severely localized electronic and magnetic states. The electron hopping between the localized states dominates the conductivity of the Sr2 Ir1− x Mn x O4 samples.